Cetacean sightings from the British Antarctic Survey CCAMLR synoptic krill survey of South Georgia and the South Sandwich Islands, January to February 2019 - Baines, Mick; Reichelt, Maren; Lacey, Claire; Pinder, Simon; Fielding, Sophie; Jackson, Jennifer A (NERC EDS UK Polar Data Centre, 2021)
Cetacean sightings in South Georgia and South Sandwich Islands waters, made by a team of four professional marine mammal observers during the British Antarctic Survey CCAMLR synoptic krill survey on the RRS James Cook (DY098), January and February 2019. The latitude and longitude of each sighting, the identified species, bearing and distance from the vessel, and estimated group size are provided. These data have been used by BAS to estimate (i) humpback whale and (ii) baleen whale abundance in South Georgia and South Sandwich Islands waters in 2019. Funding provided by the Foreign, Commonwealth and Development Office, as part of the Overseas Territories Blue Belt programme, as well as the South Georgia Heritage Trust and Darwin PLUS award DPLUS057. : Sightings data were collated in the LOGGER database, using standard cetacean sighting survey protocols as detailed in the associated document "Discovery survey protocol final" and in the publication associated with these data. Distance sampling surveys took place whilst the vessel was making way (speed approx. 9 knots), there was sufficient daylight, wind speed was less than 27 knots and sea state is less than Beaufort 6. Surveys did not take place when krill trawls were in progress. Whilst on effort, there were a minimum of two observers on watch at all times and one data recorder (DR) recording sightings. Watches ran throughout the day, to maximise the time available within the constraints of the working hours specified by the UK's Natural Environment Research Council. Watch periods did not run for more than 12 hours and within that were flexible according to survey constraints and weather. The survey team rotated position every hour, with each observer spending one hour watching and the following hour either as DR or off watch, to minimise exposure. In conditions where cold exposure was heightened, the watch period was reduced to 30 minutes. Observers searched with naked eyes, scanning their search area in a consistent manner without focussing on particular regions-but making particular effort to watch directly ahead (i.e., the trackline) as much as possible. The trackline in front of the survey vessel was the sector of primary interest (for distance sampling purposes), but the sides were not neglected. The following search pattern was employed: - Port observer: searched the area from 90° port to about 10° starboard, - Starboard observer: searched the area from 90° starboard to about 10° port. This ensured that the trackline was covered by both observers. All species of cetacean were recorded. The main responsibility of the observer team was to obtain accurate information on the time, angle, radial distance, species identification and school size of as many cetacean sightings as possible. Each observer used 7x50 binoculars with reticles, a watch set to UTC and paper sightings forms & pencils to be used if LOGGER failed. Angle boards were mounted to the platform to assist with bearing identification (0 indicating directly ahead of the vessel). Radial distances to sightings were estimated using reticles to measure distance from the horizon. Angles from the trackline to the sighting were read from pointers on the mounted angle boards. At the point of the sighting, the DR also noted the direct heading of the vessel in case it differed from bearing of the vessel track (i.e. due to weather conditions). The Bridge, any ornithologists, crew or other observers were instructed not to indicate any sightings to the observers. On detecting a cue, the observer immediately informed the data recorder that they have a sighting via UHF radio. The data recorder then recorded the information straight into LOGGER. Sighting numbers are assigned in LOGGER automatically. When one observer made a detection, the other observer kept searching in their usual way unless assistance with taxonomic ID was requested. Re-sightings of the same animals were not recorded. : Sighting data were collated using LOGGER software version 2010. Each observer used 7x50 binoculars with reticles. : Data collection and QC are detailed in "Discovery survey protocol final". Where species identification was unclear, sightings were described as "unidentified whale" or similar.